Identification of novel microRNAs in the sheep heart and their regulation in heart failure - Lee Lee Wong (Nature Portfolio, 2017)
Abstract Study of microRNA (miRNAs) using sheep models is limited due to lack of miRNA information. We therefore investigated oar-miRNAs and their regulation in an ovine model of heart failure (HF). Left ventricular (LV) tissue was collected from normal (Cont), HF (LV pacing @ ~220bpm for 13-days) and HF-recovery sheep (HF-R, 26-days after pacing cessation). MiRNA expression was profiled using next-generation sequencing (NGS) and miRNA array, and validated by stem-loop qPCR. Detected sequences were mapped against the ovine genome (Oar v4.0) and aligned with known miRNAs (miRBase v21). A total of 36,438,340 raw reads were obtained with a peak distribution of 18–23 nt. Of these, 637 miRNAs were detected by NGS and mapped to the ovine genome. With cut-off at 10 counts, 275 novel miRNAs were identified (with 186 showing 100% alignment and 89 showing 70–99% alignment with human/mouse and/or rat miRNAs, respectively), and 78 known oar-miRNAs. Cardiac-enriched miRNA-1, -133a, -208a/b and -499 were highly expressed in the LV. With HF induction, miRNA-133b-3p, -208b-3p, -125a-5p, -125b-5p, -126-3p, -21-5p, -210-3p, -29a-3p, -320a and -494-3p were significantly up-regulated relative to Cont and tended to return to normal levels following HF-recovery. This study has expanded the sheep miRNA database, and demonstrated HF-induced regulation of miRNAs.